Implementación de un sistema de control de inventarios para la ferretería materiales de construcción Aldair ubicada cantón El Chaco, provincia de Napo - Tipantiza Andy, Ligia Amparo (2016)
This research had as main objective to propose the implementation of an Inventory Control System for ALDAIR Building Materials Hardware Store, considering the policies, procedures, roles and responsibilities of personnel associated with inventory management, with the purpose to facilitate the financial management and administrative resources through functions and procedures manual, in the same the hierarchy charges are defined, it determines the functions objectively and methods and technical procedures are established to achieve the objectives. Methods and techniques were used, which allowed to identify the responsibilities and separation of functions within the organization….